2014
DOI: 10.32607/20758251-2014-6-1-54-60
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Induced Pluripotent Stem Cells for SOD1-Associated Amyotrophic Lateral Sclerosis Pathogenesis Studies

Abstract: The genetic reprogramming technology allows one to generate pluripotent stem cells for individual patients. These cells, called induced pluripotent stem cells (iPSCs), can be an unlimited source of specialized cell types for the body. Thus, autologous somatic cell replacement therapy becomes possible, as well as the generation of in vitro cell models for studying the mechanisms of disease pathogenesis and drug discovery. Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disorder that leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 25 publications
1
19
0
1
Order By: Relevance
“…These non-neuronal cells associated with peripheral motor nerves may provide additional information related to the pathogenic mechanisms of sporadic ALS once hiPSC-derived motor neurons could be produced from them. Of note, the growth and differentiation of peripheral motor nerve fibroblast-derived hiPSCs shown in this work seemed to be comparable to those hiPSCs derived from adult skin fibroblasts described elsewhere (Chestkov et al, 2014 ).…”
Section: Discussionsupporting
confidence: 85%
“…These non-neuronal cells associated with peripheral motor nerves may provide additional information related to the pathogenic mechanisms of sporadic ALS once hiPSC-derived motor neurons could be produced from them. Of note, the growth and differentiation of peripheral motor nerve fibroblast-derived hiPSCs shown in this work seemed to be comparable to those hiPSCs derived from adult skin fibroblasts described elsewhere (Chestkov et al, 2014 ).…”
Section: Discussionsupporting
confidence: 85%
“…This appeared to be related to neurofilament misregulation and also resulted in axonal pathology in the affected cells (Chen et al, 2014). Other iPSC-lines from patients carrying SOD1 mutations have been created including the SOD1 L144F mutation (detailed as part of the discussion on iPSC-derived motor neuron differentiation)(Dimos et al, 2008) and more recently SOD1 N87S and SOD1 S106L (Chestkov et al, 2014)…”
Section: Human Ipsc-derived Neural Cells For In Vitro Als Modeling (Fmentioning
confidence: 99%
“…Previous studies have shown that removing some obstacles [ 69 - 73 ] and activating innate immunity [ 74 ] could promote reprogramming efficiency, and using piggyBac (PB) transposition could eliminate the potential dangers of insertion [ 75 - 79 ]. Moreover, besides obtaining iPS cells from blood [ 80 ] and primary skin fibroblasts [ 81 ], generating a non-viral human iPS cell bank from donors has been achieved [ 82 ], based on previous virus-based methods [ 83 - 86 ]. Considering the rapid progress of this area, involving safer, more affordable, more efficient, and more convenient protocols, it is conceivable that this methodology will in the near future be used clinically, for various human tissues.…”
Section: Applications and Expectationsmentioning
confidence: 99%